Analysis of the Gap Between Higher Education and Industry 4.0 Job Market - Abdulzada, Zarnishan; Ziaei Nafchi, Majid; Pavlíček, Antonín, 1977-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
The fourth industrial revolution refers a significant transformation in human history, characterized by noticeable shift in how we manage our lives, professions, and interactions. It represents a new era led by innovative advancements in technology mirroring the influence of the first three industrial revolutions. As traditional roles evolve or disappear, adapting to new technologies and workflows becomes critical for graduates. Characterized by emergence of new technologies including cyber-physical systems, automation, cloud computing, cybersecurity, augmented reality, additive manufacturing, simulation, big data, artificial intelligence, Internet of Things, Industry 4.0 has completely changed the market demand for jobs currently, with new skills and competencies required for graduates entering this more digitalized and automated workforce. This thesis studies the correspondence between higher education curriculums and the specific requirements of the job market of Industry 4.0 in the Czech Republic. Comparing curriculum analysis with market data analysis mixed methods approach is used to identify the industry trends and the universities’ dedication to prepare competent graduates to compete in the market. It aims to assess the extent to which universities are preparing graduates with the skills and knowledge demanded by employers, identify collaboration practices between academic institutions and industry partners, and highlight any gaps in competency between graduate capabilities and job market expectations. The study is concluded with suggested recommendations to address these gaps and ensure that graduates are equipped with necessary skills.
Vedoucí práce: Majid Ziaei Nafchi
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management of business informatics [obor dipl. práce]; diplomové práce; master's theses